Pengembangan Kreativitas dan Literasi Media Sosial Youtube melalui Konten Video Bagi Siswa - Fauzaan, Ryan Ardhiansyah Nur; Nurhadi, Zikri Fachrul (Penerbit Goodwood, 2024)
Purpose: The background of this service is the discovery that creativity and literacy in YouTube social media are currently still low. The purpose of implementing this service is to improve students' creativity and literacy by deepening their understanding of the content on YouTube social media and as a means of channeling ideas, talents, and interests of students at SMP 1 Cibatu.Methodology/approach: The method used in implementing this activity is a seminar on developing creativity and social media literacy on June 14 2024 with counseling and mentoring.Results/findings: The results of this community service activity increased by 61.29% from 25.81% to 87.10% of students knowing the creativity and literacy of social media, especially on YouTube. Apart from that, it motivates students to continue working to express ideas in content production concepts, create concepts that students are interested in, and carry out the content creation process itself. Conclusions: In conclusion, this can significantly improve students' creativity.Limitations: The limitations of this service are that it only focuses on developing creativity and YouTube social media literacy, so that students can have innate abilities that focus on how to create content.Contribution: The results of this community service contribute especially to students who already have basic skills in how to create video content, this can provide new insights and knowledge to increase their creativity.